Outcomes after percutaneous coronary intervention of ostial lesions in the era of drug-eluting stents - Freeman, M.; Clark, D.; Andrianopoulos, N.; Duffy, S.; Lim, H.; Brennan, A.; Charter, K.; Shaw, J.; Horrigan, M.; Ajani, A.; Sebastian, M.; Reid, Christopher; et al. (2009)
Background: Ostial lesions are a difficult subset associated with suboptimal outcomes after percutaneous coronary intervention (PCI). The aim of this study was to analyze outcomes of ostial lesions in contemporary Australian interventional practice. Methods: The study population comprised 1,713 consecutive patients who underwent PCI for proximal lesions of the left anterior descending, left circumflex, and right coronary arteries, who were prospectively enrolled in the Melbourne Interventional Group Registry (February 2004-December 2006). We compared the in-hospital, 30-day, and 1-year outcomes of the 109 patients undergoing PCI for ostial, with the 1,604 patients with proximal nonostial lesions. Left main and bifurcation lesions were excluded. Results: Patients in the ostial group were older (mean age 68.8 ± 11 vs. 64.9 ± 12 years; P = 0.001), and there was a greater proportion of women (38.5% vs. 28.0%; P = 0.021). Other clinical characteristics were similar. The nonostial group were more likely receive a stent (94.6% vs. 87.2%; P = 0.005) but drug-eluting stents (DES) were deployed more often in the ostial group (47.9% vs. 66.1%; P < 0.0001). There was lower procedural success, with no significant difference in in-hospital death, bleeding or emergency PCI, but unplanned in-hospital coronary artery bypass grafting was more frequent in the ostial group (4.8% vs. 1.0%; P = 0.007). There was no difference in 30-day major adverse cardiac events. However, 12-month death (8.8% vs. 4%, log rank P = 0.032) and MACE (24.2% vs. 13.8%, log rank P = 0.005) were higher in the ostial group than the nonostial group with trends to increased incidence of myocardial infarction (6.6% vs. 4.7%, P = NS), and target vessel revascularization (13.2% vs. 7.9%, P = NS). Conclusion: In contemporary, Australian interventional practice, PCI for ostial lesions is associated with a high incidence of adverse outcome at one year despite the introduction of DES. © 2009 Wiley-Liss, Inc.